Pre-Pregnancy Body Mass Index and the Risk of Hyperemesis Gravidarum: A Systematic Review and Meta-Analysis - Ensiyeh Jenabi; Amir Mohammad Salehi; Soodabeh Aghababaei; Salman Khazaei (Clinical and Experimental Obstetrics & Gynecology)
Background: Hyperemesis gravidarum (HG) is an infrequent and severe occurrence of nausea and/or vomiting during pregnancy, with a prevalence ranging from 0.3% to 2%. Until now, no meta-analytic study has been undertaken to assess the correlation between pre-pregnancy body mass index (BMI) and the likelihood of HG. Consequently, this meta-analysis was carried out to examine the connection between BMI and HG risk. Methods: For this systematic review and meta-analysis, we conducted a thorough search of electronic bibliographic databases such as PubMed, Web of Science, Scopus, and Science Direct until May 2022. The outcomes were presented utilizing a random-effects model. Heterogeneity was assessed using the chi-square test and I2 statistic. Potential publication bias was examined using Begg’s test. Additionally, we evaluated the quality of studies using the Newcastle Ottawa Scale. Results: In total, seven studies were included in the present meta-analysis such as six cohort studies and one cross-sectional study. In this meta-analysis, 3,573,663 participants were involved. Based on the results, the underweight was a risk factor for HG (odds ratio (OR) = 1.91, 95% confidence interval (CI): 1.21, 2.61). There was not significant association between overweigh and HG (OR = 1.23, 95% CI: 0.96, 1.50). In addition, there was not significant association between obesity and HG (OR = 0.88, 95% CI: 0.42, 1.34). Heterogeneity was seen among the included studies. Conclusions: An apparent association between pre-pregnancy BMI and the risk of HG has been observed. However, further investigation is necessary, as the mechanisms and the connection to GDF15 are not yet clear. The most supported public health advice is to attain a healthy BMI before conception. Additionally, the oversight of confounding variables should be taken into account, highlighting the need for comprehensive consideration in future studies.